Calpain-1 and Calpain-2 in the Brain: New Evidence for a Critical Role of Calpain-2 in Neuronal Death - Wang, Yubin (Cells, 2020)
Calpains are a family of soluble calcium-dependent proteases that are involved in multiple regulatory pathways. Our laboratory has focused on the understanding of the functions of two ubiquitous calpain isoforms, calpain-1 and calpain-2, in the brain. Results obtained over the last 30 years led to the remarkable conclusion that these two calpain isoforms exhibit opposite functions in the brain. Calpain-1 activation is required for certain forms of synaptic plasticity and corresponding types of learning and memory, while calpain-2 activation limits the extent of plasticity and learning. Calpain-1 is neuroprotective both during postnatal development and in adulthood, while calpain-2 is neurodegenerative. Several key protein targets participating in these opposite functions have been identified and linked to known pathways involved in synaptic plasticity and neuroprotection/neurodegeneration. We have proposed the hypothesis that the existence of different PDZ (PSD-95, DLG and ZO-1) binding domains in the C-terminal of calpain-1 and calpain-2 is responsible for their association with different signaling pathways and thereby their different functions. Results with calpain-2 knock-out mice or with mice treated with a selective calpain-2 inhibitor indicate that calpain-2 is a potential therapeutic target in various forms of neurodegeneration, including traumatic brain injury and repeated concussions.